Association between emergency department utilization and the risk of child maltreatment in young children - Xiaoxin Kuang; Yumiko Aratani; Guohua Li (Injury Epidemiology, 2018)
Abstract Background This study aims to assess the association between emergency department (ED) utilization and the risk of child maltreatment. Methods Using ED discharge data from the California’s Office of Statewide Health Planning (OSHPD) and Development for 2008–2013, we performed a nested case-control study to examine the relationship between the frequency of ED visits and child maltreatment diagnosis under 4 years of age among children born in California between 2008 and 2009 who visited the ED. Results The study sample consisted of 3772 children diagnosed with child maltreatment (cases) and 7544 children selected by incidence density sampling (controls). After adjustment for demographic characteristics, the estimated odds ratios of child maltreatment were 1.72 (95% CI:1.55–1.90) for those with two to three ED visits and 3.03 (95% CI: 2.69–3.41) for those with four or more ED visits, compared to children with one visit. Race/ethnicity, insurance status, and location of residence were also significantly associated with the risk of child maltreatment. Conclusions Young children with higher frequency of ED visits are at significantly increased risk of being victims of child maltreatment. ED utilization patterns and other established risk markers may assist healthcare professionals in identifying and treating victims of child maltreatment.